Cardiolipin Synthesis in Skeletal Muscle Is Rhythmic and Modifiable by Age and Diet. (15th June 2020) - Nohara, Kazunari; Kim, Eunju; Wirianto, Marvin; Mileykovskaya, Eugenia; Dowhan, William; Chen, Zheng; Yoo, Seung-Hee
Abstract : Circadian clocks regulate metabolic processes in a tissue-specific manner, which deteriorates during aging. Skeletal muscle is the largest metabolic organ in our body, and our previous studies highlight a key role of circadian regulation of skeletal muscle mitochondria in healthy aging. However, a possible circadian regulation of cardiolipin (CL), the signature lipid class in the mitochondrial inner membrane, remains largely unclear. Here, we show that CL levels oscillate during the diurnal cycle in C2C12 myotubes. Disruption of the Ror genes, encoding the ROR nuclear receptors in the secondary loop of the circadian oscillator, in C2C12 cells was found to dampen core circadian gene expression. Importantly, several genes involved in CL synthesis, including Taz and Ptpmt1, displayed rhythmic expression which was disrupted or diminished in Ror-deficient C2C12 cells. In vivo studies using skeletal muscle tissues collected from young and aged mice showed diverse effects of the clock and aging on the oscillatory expression of CL genes, and CL levels in skeletal muscle were enhanced in aged mice relative to young mice. Finally, consistent with a regulatory role of RORs, Nobiletin, a natural agonist of RORs, was found to partially restore transcripts levels of CL synthesis genes in aged muscle under a dietary challenge condition. Together, these observations highlight a rhythmic CL synthesis in skeletal muscle that is dependent on RORs and modifiable by age and diet.